Planet earth. - Crawford, Jean Burke (Alexandria, Virginia : Time-Life Books, 1997)
Describes the earth sciences and examines volcanoes, earthquakes, mountains, rivers, lakes, oceans, rocks, minerals, weather, and the atmosphere.
Includes index.
NLP
Keywords: Earth sciences -- Juvenile literature